Emerging histopathological parameters in the prognosis of oral squamous cell carcinomas - de Morais (Spain, 2025)
Oral squamous cell carcinoma (OSCC) is the most common oral malignancy, representing 90% of all malignant neoplasms in the head and neck region. Patients with this aggressive tumor have an overall 5-year survival rate of approximately 50%, which drops to less than 30% when tumors are diagnosed at advanced clinical stages. Over decades, several studies provided high-level evidence of the impact of histopathological features on treatment guidelines and prognosis of OSCC. The 8th American Joint Committee on Cancer (AJCC) TNM staging system recognized the importance of depth of invasion to the T category and extranodal extension to the N category for OSCC. This review provides the current knowledge on emerging histopathological parameters identified as potential biomarkers for OSCC, such as depth of invasion, tumor thickness, the pattern of invasion, inflammatory profile, and tumor-stroma ratio, evaluating their clinical relevance on patient outcomes. Analysis, limitations, and potential biological mechanisms are highlighted and discussed. Assessing and reporting these markers are cost-effective and can be incorporated into daily practice.